First complete mitochondrial genome of the endemic goby, Rhinogobius davidi (Gobiiformes: Gobiidae: Gobionellinae), in China. Issue 3 (4th March 2023) - Song, Lin; Chen, Xiao Jiang; Song, Yang; Wang, Quan
Abstract: The first complete mitochondrial genome of the freshwater goby Rhinogobius davidi was determined by high-throughput sequencing. This genome was 16, 627 bp in length and consisted of 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and 2 non-coding control regions. Phylogenetic analysis based on the amino acid sequences of 13 mitochondrial protein-coding genes from R. davidi and 23 relatives suggested that R. davidi had a close mitogenome relationship with Rhinogobius giurinus . This complete genome of R. davidi will provide basal molecular data for future studies on taxonomy, comparative genomics, and adaptive evolution in Rhinogobius .